The footprint of orthostatic hypotension in parkinsonian syndromes. (August 2020) - Raccagni, Cecilia; Sidoroff, Victoria; Goebel, Georg; Granata, Roberta; Leys, Fabian; Klucken, Jochen; Eskofier, Bjoern; Richer, Robert; Seppi, Klaus; Wenning, Gregor K.; Fanciulli, Alessandra
Highlights: Orthostatic hypotension may worsen gait performance in Parkinson's disease and multiple system atrophy. Gait impairment correlates with the fall in blood pressure upon standing. Wearable sensors detect the impact of orthostatic hypotension on gait.